KAJIAN ANALISIS HADIST SUNAN IBN MAJAH; ILMU PENGETAHUAN DAN KEUTAMAAN ORANG BERILMU DALAM PERSEPEKTIF HADIST - Muhammad Rendi Ramdhani (Program Studi Manajemen Pendidikan Islam, 2024)
This research aims to find out and explain science and the virtues of knowledgeable people from the perspective of the hadith of the Prophet Muhammad SAW, namely in Sunan Ibn Majah. The method used is the library research method (Library Research) by taking literature that is appropriate to the subject of discussion in the form of books, journal articles, both national and international which will later be analyzed in depth so that conclusions and findings can be drawn in the research. The research results show that there are 5 points that are the priority of knowledgeable people as explained in Sunan Ibn Majah, namely: 1) Getting an easy way to heaven. 2) Favored by angels. 3) Begged for forgiveness by other creatures of Allah. 4) More important than worshipers, and 5) Being the heir of the prophet. This research concludes that having knowledge for Muslims is very important because its priority factor is also a command from Allah SWT. And the superiority of people who have knowledge is due to the nobleness of that knowledge which becomes an intermediary for its claimants towards goodness, piety and eternal luck.